SHORTENED STAPEDIUS TENDON: A RARE CAUSE OF CONDUCTIVE HEARING LOSS – A CASE REPORT - Lutfullaevа Gulnoza Umrilloevna (Western European Studies, 2025)
Anomalies of the stapedius tendon have been reported to cause conductive hearing loss, as such anomalies theoretically limit the movement of the stapes.
Keywords: Conductive Hearing Loss; Stapedius; Tendons